Bacterial Communities Associated with Four Cyanobacterial Genera Display Structural and Functional Differences: Evidence from an Experimental Approach - Zhu, Lin; Zancarini, Anouk; Louati, Imen; De Cesare, Silvia; Duval, Charlotte; Tambosco, Kevin; Bernard, Cécile; Debroas, Didier; Song, Lirong; Leloup, Julie; Humbert, Jean-François (Frontiers in Microbiology, 2016)
To overcome the limitations associated with studying the interactions between bacterial communities (BCs) and cyanobacteria in natural environments, we compared the structural and functional diversities of the BCs associated with fifteen non-axenic cyanobacterial strains in culture and two natural BCs sampled during cyanobacterial blooms. No significant differences in richness and diversity were found between the natural and cultivated BCs, although some of the cyanobacterial strains had been isolated 11 years earlier. Moreover, these BCs shared some similar characteristics, such as a very low abundance of Actinobacteria, but they display significant differences at the OTU level. Overall, our findings suggest that BCs associated with cyanobacteria in culture are good models to better understand the interactions between heterotrophic bacteria and cyanobacteria. Additionally, BCs associated with heterocystous cyanobacterial strains cultivated in Z8X culture medium without nitrate (Aphanizomenon-Dolichospermum) demonstrated significant differences compared to BCs associated with non-heterocystous strains cultivated in Z8 culture medium (Planktothrix-Microcystis) in terms of their composition and their ability to utilize different carbon sources, suggesting the potential influence of cyanobacterial metabolism and/or culture media on associated BCs. Finally, half of the dominant operational taxonomic units (OTUs) in these BCs were specifically associated with cyanobacteria or other phytoplankton, whereas the remaining OTUs were generally associated with ecosystems containing high Organic Matter (OM) content, such as sludge or intestines.